2019
DOI: 10.1002/mgg3.673
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NEAT1 regulates the development of osteosarcoma through sponging miR‐34a‐5p to mediate HOXA13 expression as a competitive endogenous RNA

Abstract: Background Long noncoding RNA (lncRNA) exerts a potential regulatory role in tumorigenesis. LncRNA NEAT1 expression remains high in osteosarcoma tissues. However, its biological mechanism in osteosarcoma remains unknown. Methods In this study, NEAT1 expression in osteosarcoma cells was detected by qRT‐PCR. Proliferative and apoptosis potentials of osteosarcoma cells were determined by CCK‐8 assay and Flow Cytometry, respectively. We identified the potential target of NEAT1 through bioinformatics and dual‐lucif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…lncRNAs have been reported to sponge miRNAs via a competitive endogenous mechanism, thus antagonizing the function of miRNAs ( 52 ). NEAT1 upregulates Homeobox A13 by targeting miR-34a-5p and regulates the development of osteosarcoma ( 53 ). NEAT1 also promotes cervical cancer cell proliferation by sponging miR-9-5p ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs have been reported to sponge miRNAs via a competitive endogenous mechanism, thus antagonizing the function of miRNAs ( 52 ). NEAT1 upregulates Homeobox A13 by targeting miR-34a-5p and regulates the development of osteosarcoma ( 53 ). NEAT1 also promotes cervical cancer cell proliferation by sponging miR-9-5p ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“… 28 Dysregulated lncRNAs have been confirmed to be relevant to the disease development. 29 Recent studies suggested that lncRNAs might serve as effective therapeutic targets for OS treatment. 16 , 30 , 31 In this study, we found that lncRNA HCG11 was highly expressed in OS related to the counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer's large tumor heterogeneity and its low prevalence make it tough to gain meaningful progress in patient's survival [28]. Dysregulated lncRNAs have been confirmed to be relevant to the disease development [29]. Recent studies suggested that lncRNAs might serve as effective therapeutic targets for OS treatment [15,18,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different studies indicated that lncRNA NEAT1 dysregulation boosted tumorigenesis in a variety of human malignancies, including OS. For example, Ji et al found that lncRNA NEAT1 participated in the development of OS as a ceRNA sponging to miR-34a-5p and thus regulate HOXA13 expression [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation